ANALISIS MODEL KEPUASAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA UD USAHA SARI - Trisna Dewi, Ni Kadek Ayu; Amelia Ardiani, Kadek Ayu (Komunitas Manajemen Kompetitif, 2023)
This study aims to determine the model analysis of customer satisfaction on purchasingdecisions at UD Usaha Sari. With a population of consumers who use the services of UD UsahaSari and a sample of 80 consumers. Data analysis techniques used in this study are validity test,reliability test, multiple linear regression analysis,classical assumption test, model feasibility test(Goodness Of Fit) and hypothesis testing (T-Test). The results of this study indicate that the effectof product diversity on purchasing decisions at UD Usaha Sari is 0.175 units or 11.5% and theeffect of product diversity on purchasing decisions and the results of hypothesis testing with theT-Test test show that t-count > t-table (2.558 > 1.664). The effect of price on purchasingdecisions at UD Usaha Sari is 0.267 units or 16.9% and the effect of priceon purchasing decisionsand the results of testing the hypothesis with the T-Test test show that t-count > t-table (2.827 >1.664). The effect of promotion on purchasing decisions at UD Usaha Sari has a regression valueof 0.526 units or 46.5% and the effect of promotion on purchasing decisions and the results oftesting the hypothesis with the T-Test test found that t-count> t-table (7.305> 1.664) . Based onthecalculation results, it is known that the value of F-count > F-table, (75.529 > 3.11) indicatesthat the analysis of the model of consumer satisfaction consisting of productdiversity, prices andpromotions has an effect on purchasing decisions with a significant value of 0.000 <0.050.